Synthesis and spectral investigation of some methyl-substituted 3-(2-pyridyl)-2-(2-thienyl)thiazolidin-4-one derivatives - Fidan, Ismail; Kazaz, Cavit; Sahin, Ertan; Kaban, Seniz (SCIENCE REVIEWS 2000 LTD, 2010)
Some heteroaryl-substituted thiazolidin-4-one derivatives have been synthesised starting from thiophenecarbox-aldehydes, 2-amino-6-methylpyridine and 2-mercaptoacetic acid. However, the use of 2-mercaptopropanoic acid gave the thiazolidinone derivatives as a mixture of cis-and trans-isomers. The configuration of both the cis-and trans-isomers has been established by NOE-difference experiments. Furthermore, the stereochemistry of one of the trans isomers was established by X-ray crystallography.
Keywords: heteroaryl-substituted thiazolidinone; configuration; diastereomer; NOE-difference; X-ray crystallography; POTENTIAL ANTITUMOR-ACTIVITY; 4-THIAZOLIDONE DERIVATIVES; ANTICONVULSANT PROPERTIES; AGENTS; Chemistry